Simultaneous bilateral laparoscopic cortical-sparing adrenalectomy for bilateral pheochromocytomas in multiple endocrine neoplasia type 2 - Qi, Xiao-Ping; Lian, Bi-Jun; Fang, Xu-Dong; Dong, Fang; Li, Feng; Jin, Hang-Yang; Zhang, Ke; Wang, Kang-Er; Zhang, Yi (Frontiers in Surgery, 2023)
Purpose: To assess the feasibility of simultaneous bilateral laparoscopic or open cortical-sparing adrenalectomy (SB-LCSA or SB-OCSA) for bilateral pheochromocytomas (bPHEO) in multiple endocrine neoplasia type 2 (MEN2). Methods: A total of 31 patients (54.8% women) were diagnosed with MEN2 related bPHEO, and 29 of them underwent varying specific adrenal surgery. We systematically analyzed and evaluated their clinical profiles, mutation types, tumor histopathologic features, and follow-up records. Results: All 31 patients with bPHEO were associated with RET-C634(90.3%) and RET-M918T (9.7%) mutations and the median age at initial presentation was 38 years (range, 23–78). Therein, the appearance of the bPHEO in 27 patients were synchronous and the other 4 (12.9%) were metachronous. A total of 29 patients underwent initial CSA including 23 (79.3%) undergoing synchronous bilateral CSA(18 SB-LCSA and 5 SB-OCSA) and 6 (20.7%) undergoing metachronous CSA. There were less bleeding volume and shorter hospitalizations between SB-LCSA and SB-OCSA, as well as synchronous surgery versus metachronous surgery (all P < 0.05). Corticosteroid replacement treatment was necessary for 14 patients (45.2%) after the bilateral CSA. During a median follow-up period of 7 years (range, 1.8–23), 3 of these patients (10.3%) showed a recurrent disease and reoperation was needed. Conclusions: SB-LCSA for treatment of synchronous bPHEO is feasible and should be recommended as a prioritized surgical approach.